Estrogen administration modulates hippocampal GABAergic subpopulations in the hippocampus of trimethyltin-treated rats - Corvino, Valentina; Di Maria, Valentina; Marchese, Elisa; Lattanzi, Wanda; Biamonte, Filippo; Michetti, Fabrizio; Geloso, Maria Concetta (Frontiers in Cellular Neuroscience, 2015)
Given the well-documented involvement of estrogens in the modulation of hippocampal functions in both physiological and pathological conditions, the present study investigates the effects of 17-beta estradiol (E2) administration in the rat model of hippocampal neurodegeneration induced by trimethyltin (TMT) administration (8mg/kg), characterized by loss of pyramidal neurons in CA1, CA3/hilus hippocampal subfields associated with astroglial and microglial activation, seizures and cognitive impairment. After TMT/saline treatment, ovariectomized animals received two doses of E2 (0.2 mg/kg i.p.) or vehicle, and were sacrificed 48h or 7 days after TMT-treatment. Our results indicate that in TMT-treated animals E2 administration induces the early (48h) upregulation of genes involved in neuroprotection and synaptogenesis, namely Bcl2, trkB, Cadherin and cyclin-dependent-kinase-5. Increased expression levels of glutamic acid decarboxylase (gad) 67, neuropeptide Y (Npy), parvalbumin , Pgc-1α and Sirtuin 1genes, the latter involved in parvalbumin (PV) synthesis, were also evident. Unbiased stereology performed on rats sacrificed 7 days after TMT treatment showed that although E2 does not significantly influence the extent of TMT-induced neuronal death, significantly enhances the TMT-induced modulation of GABAergic interneuron population size in selected hippocampal subfields. In particular, E2 administration causes, in TMT treated rats, a significant increase in the number of GAD67-expressing interneurons in CA1 stratum oriens, CA3 pyramidal layer, hilus and dentate gyrus, accompanied by a parallel increase in NPY-expressing cells, essentially in the same regions, and of PV-positive cells in CA1 pyramidal layer. The present results add information concerning the role of in vivo E2 administration on mechanisms involved in cellular plasticity in the adult brain.